Complex diffraction and dispersion effects in femtosecond laser writing of fiber Bragg gratings using the phase mask technique - Abdukerim, Nurmemet; Grobnic, Dan; Lausten, Rune; Hnatovsky, Cyril; Mihailov, Stephen J (Optics express, 2019)
The combined effect of chromatic dispersion and conical diffraction (i.e., off-plane diffraction) in femtosecond laser inscription of fiber Bragg gratings using the phase mask technique is characterized by measuring the light intensity distribution after the phase mask. As the distance from the mask and the observation point grows, chromatic dispersion and conical diffraction introduced by the mask gradually decrease the peak intensity inside the line-shaped focal volume of the cylindrical lens that is used to focus the femtosecond pulses inside the fiber. We also show that at a certain distance from the mask spherical aberration introduced by the plane-parallel mask substrate is cancelled out by conical diffraction and, at a different distance, chromatic aberration of the cylindrical lens is cancelled out by chromatic dispersion of the mask. These two independent cancellation effects lead to sharpening of the line-shaped focus and the consequent growth of peak light intensity inside it. The above phenomena become especially pronounced for tightly focused femtosecond laser beams and small-pitch phase masks, which, in turn, allows one to choose experimental conditions to inscribe Bragg gratings in polymer-coated non-sensitized 50 µm fibers.